Pengaruh Lingkungan Kerja dan Pengalaman Kerja Terhadap Kinerja Pegawai pada Kantor Dinas Pendidikan, Kebudayaan, Pemuda dan Olahraga (DIKBUDPORA) Kabupaten Bima - M. Taufikurrahman; Khairul Amar; Firmansyah Kusumayadi (Indo Publishing, 2026)
This study aims to examine the effect of the work environment and work experience on employee performance at the Office of the Department of Education, Culture, Youth, and Sports (DIKBUDPORA) of Bima Regency. This research employed a quantitative approach with an associative research design. The population consisted of 152 employees, while the sample comprised 60 Civil Servants (PNS) selected using a purposive sampling technique. Data were collected through observation, questionnaires, and literature review. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t-test, and F-test with the assistance of SPSS software. The results of the study indicate that, partially, the work environment does not have a positive and significant effect on employee performance, with a t-value of 1.800 < t-table of 2.002 and a significance value of 0.077 > 0.05; therefore, the first hypothesis was rejected. Meanwhile, work experience has a positive and significant effect on employee performance, with a t-value of 2.587 > t-table of 2.002 and a significance value of 0.012 < 0.05; therefore, the second hypothesis was accepted. Simultaneously, the work environment and work experience have a positive and significant effect on employee performance, with an F-value of 7.251 > F-table of 3.159 and a significance value of 0.002 < 0.05; therefore, the third hypothesis was accepted. The coefficient of determination (R²) of 0.203 indicates that the work environment and work experience explain 20.3% of the variation in employee performance, while the remaining 79.7% is influenced by other factors not examined in this study.